PERILAKU ANAK AUTIS : PERKEMBANGAN DAN PENANGAN - Armanila Sri Inda Lestari Veryawan; Sri Inda Lestari; Indah; Veryawan (Universitas Ngudi Waluyo, 2023)
R.A Baiturrofiqoh there is one hyperactive autistic child, therefore the researchers tried to examine this which aims to find out how the development of autistic children, stimulation of handling autistic children is clarified by supporting factors and inhibiting wear and tear in early childhood. The results of this study are the development of autistic children has begun to calm down when learning with teacher handling stimulation, namely trying to provide learning that is easily accepted by autistic children as well as inhibiting factors for children with learning difficulties and supporting factors for children or women. This study uses a descriptive qualitative research method in which all data were obtained through observation, interviews and documentation in accordance with the problem to be studied. Therefore, researchers hope to help teachers in teaching autistic children.Â Â